Magnetic Force Microscopy (MFM) Characterization of Superparamagnetic Nanoparticles (SPIONs) - Cordova, Gustavo (University of Waterloo, 2012)
Superparamagnetic iron oxide nanoparticles (SPIONs), due to their controllable sizes, relatively long in vivo half-life and limited agglomeration are ideal for biomedical applications such as magnetic labeling, hyperthermia cancer treatment, targeted drug delivery and for magnetic resonance imaging (MRI) as contrast enhancement agents. However, very limited studies exist on detecting and characterizing these SPIONs in vitro in physiologically relevant conditions. It would be of interest to localize and characterize individual SPIONs at the nanoscale in physiologically relevant conditions. MFM offers great potential for this purpose. We evaluate the applicability of Magnetic Force Microscopy (MFM) in air as well as in liquid to characterize bare and SiO2 coated SPIONs on mica .The magnetic properties of bare and SiO2 coated SPIONs are compared on the nanoscale using MFM. MFM phase- shift dependence on scan height is investigated using SPION samples that have been coated in hydrophobic polymers, polystyrene (PS) and poly (methyl methacrylate) (PMMA). The polymers are used to spin-coat SPION samples and mimic cell lipid bilayers. Nanoscale MFM images of SPIONs in a liquid environment, covered with these hydrophobic polymers are also presented for the first time. The use of 3-merceptopropyltrimethoxysilane (3-MPTS) to covalently attach SiO2 SPIONs to gold substrates for the potential purpose of MFM imaging in liquid is also briefly addressed. These results will allow us to understand the feasibility of detecting magnetic nanoparticles within cell membranes without any labeling or modifications and present MFM as a potential magnetic analogue for fluorescence microscopy. These results could be applied to cell studies and will lead to a better understanding of how SPIONs interact with cell membranes and have a valuable impact for biomedical applications of all types of magnetic nanoparticles.
Keywords: MFM; magnetic nanoparticles; Biology